Knowledge Conversion Perancangan Instruksi Kerja Kegiatan Preventive Maintenance HAAS CNC Milling dengan Metode SECI - Soesanto, Rayinda Pramuditya (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2017)
Nowadays to gain a competitive advantage in an organization, knowledge becomes important as an asset that must be managed. The experience possessed by humans is tacit and sometimes difficult to extract into a procedure or standard that can be used in an organization. T University is a private university in Indonesia. At the University of T, there is a laboratory that serves as a provider of practical services for students, one of the laboratory is laboratory X. Laboratory X serves to provide an understanding in the Manufacturer process for mass production. Currently, this laboratory consists of 18 assistant labs and one laboratory staff. This laboratory has one Haas CNC Milling used in labwork activity. To keep the machine in optimum condition, good maintenance management of the facility is required especially preventive maintenance, these activities are conducted based on the experience of laboratory staff in handling Haas CNC Milling machine. The problems occur when the laboratory staff is entering the retirement period. Besides that until now there is no standard operation procedure (SOP) developed by the university about how to do preventive maintenance. This research aims to design preventive maintenance work instruction for CNC Milling Haas machine with SECI (Socialization, Externalization, Combination, and Internalization) methods. Best practice in the form of a work instruction is obtained from the process of knowledge conversion from laboratory staff and head of laboratory. From the exploration result, it is known that preventive maintenance activities for Haas CNC Milling machine consist of spindle cleaning, checking tools, lubrication check and engine coolant, and run test. Brainstorming is done to confirm and select best practices created by both speakers. From the brainstorming result, it is known that the work instructions performed by the laboratory staff are selected by modifying some aspects of checking.